Translocação dos herbicidas glyphosate e imazamox em plantas de aguapé - Campos, C. F. de [UNESP] (2013)
Eichhornia crassipes is one of the main weeds found in aquatic environments, being undesirable for many activities. The aim of this study was to evaluate the translocation of glyphosate and imazamox in E. crassipes. Eight intervals were studied for cutting leaves that received herbicides: 2, 4, 6, 8, 12 and 24 hours after application (HAA), and a treatment with no cutting (untreated). The glyphosate dose was 2,160 g a.e. ha-1 (commercial product - Rodeo) + 0.5% v v-1 Aterbane adhesive spreader and imazamox at 290.4 g i.a. ha-1 (commercial product - Clearcast). The treatments were installed in a completely randomized design with four replications. Glyphosate showed a bad control for all the periods of leaf cutting. The imazamox did not provide control within 12 HAA, while from 24 HAA onward the control was effective. There was not a great mobility of the glyphosate molecule in water hyacinth plants, a period above 24 hours being needed for a satisfactory translocation. For imazamox at least 24 hours were needed after herbicide application for the translocation to occur along with subsequent control.